Improving The Quality Of Public Services Through Work Capabilities And Implementation Of E-Government With Innovative Behavior As Mediation: Study of Operational Employees of PT. Jasa Marga Persero Tbk - Agus Pramono; Prihatin Tiyanto; Gita Sugiyarti (International Conference On Digital Advanced Tourism Management And Technology, 2023)
This research aims to analyze the influence of work ability and the application of e-government on the quality of public services both directly and indirectly through innovative behavior in PT operational staff. Marga Services. The population in this study was all employees of Jasa Marga's operational division on the island of Java. The sample size used was 100 respondents, with a sampling technique using the proportionate random sampling method. The data source used was primary data, with a questionnaire data collection method. The analysis technique used is Partial Least Square. The results of the research analysis show that work ability has a positive and significant effect on the quality of public services, the application of e-government has a positive and significant effect on the quality of public services, and innovative behavior has a positive and significant effect on the quality of public services. Work ability has a positive and significant effect on innovative behavior, and the application of e-government has a positive and significant effect on innovative behavior. The results of the mediation test show that innovative behavior variables can mediate the influence of work ability on the quality of public services, and innovative behavior can mediate the influence of e-government implementation on innovative behavior.